The Rome Statute and Islamic Law : A Comparative Analysis with Special Reference to Saudia Arabia - Alsolami, Majed, (Brill's Arab and Islamic Laws Series ;, 2025)
This book examines in depth the degree of compatibility and incompatibility between the general principles and jurisdiction of Islamic law and international criminal law (the Rome Statute). It discusses the controversy related to the non-ratification of the Rome Statute by some Islamic and Arab countries. The author analyses arguments that maintain that Islamic law cannot be compatible with international criminal law, and makes it clear that there are no fundamental differences between the principles of Islamic law and the principles of international criminal law. The book considers Saudi Arabia as a case for reference. See Less